Implikasi Erupsi Gunung Agung Terhadap Kegiatan Pariwisata Di Kawasan Pura Besakih - Aristiani, Ni Kadek Pande; Pujani, Luh Putu Kerti (JURNAL DESTINASI PARIWISATA; Vol 7 No 1 (2019): VOL 7, NO 1 (2019): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2019.v07.i01.p07, 2019)
Besakih Temple is the bigest temple in Bali located on the slopes of Mount Agung exactly in Besakih village, Rendang district, Karangasem regency. In addition to being a center of religious ceremonies at Besakih Temple there are also tourism activities. Mount Agung is the highest mountain in Bali and has several times the last eruption occurred in 2017. The researchs try to find the condition of tourism before and after the eruption of Mount Agung in the area of Besakih Temple. The research method used is qulalitative research with comparative data analysis techniques to analyze the condition of tourism before the eruption of Mount Agung and the implications of eruption Mount Agung for tourism activities in the area of Besakih Temple. The data sources, from primary data and secondary data. The concept used are concept of eruption, concept of cultural attraction, concept of the Besakih Temple as spiritual phenomenon, concept of operational, concept of the informal sector in tourism. The result of the research shows that the influence of Mount Agung eruption on tourism activity in area of Besakih Temple is viewed based on the level of tourist visit, the condition of tourist attraction, the comfort of the area, the cleanliness of the area, the operational and income of the local tour guide, the motorcycle drivers, artshop, kiosks, activity of informal tourism sector in the area of Besakih Temple. The area of Besakih Temple managers should synergize with the government and community to conduct recovery of tourism activities in the area of Besakih Temple. Keywords: Implication, Eruption, Tourism Activity, Pura Besakih